Merdeka Belajar - Kampus Merdeka Policy: How Does It Affect the Sustainability on Accounting Education in Indonesia? - Lhutfi, Iqbal; Mardiani, Rika (Fakultas Ekonomi, Universitas Negeri Semarang, 2020)
This study attempts to conduct an analysis of Merdeka Belajar - Â Kampus Merdeka's policy on how does it affect the sustainability of accounting education in Indonesia. A Semi-systematic Descriptive Literature Method analysis was used in this paper to map research areas, synthesize conditions of information, establish the direction for further research, and to classify areas where further research is required. The results of the study show this policy is expected to have better skilled and strong character students. They are expected to have more experience, knowledge, and become more competitive graduates. Despite those advantages, this policy also has potential weaknesses, namely the large number of studies taken might distract the direction of the path of study, this policy does not affect educational-based studies that are geared towards producing teachers, and regularly changing policies by every new minister pays less attention to the sustainability aspects. This paper research implies the policymakers to pay more attention to the sustainability of accounting education by considering the required aspects.